The potential of the second-hand personal luxury market in Portugal - Xavier, Maria Beatriz Sá De Miranda (2021)
The Portuguese luxury market is quite undeveloped, due to social and financial factors. Such financial factors could be mitigated through second-hand, which has had a recent global rise, yet to reach Portugal, however. In order to understand the second-hand luxury market potential in Portugal, this Work Project analyzes the behavior of Portuguese towards the market. Thereby, a qualitative and quantitative analysis were conducted to consumers. The results show untapped market potential, which differs from the global one, in terms of consumer profile, motivations, channels, shopping experience and offer. Therefore, market players should be adapted to market specifications, as to succeed.